Lightning impulse tests on air-breakdown level in point-plane electrode configuration - Che Mok @ Adnan, Mohd Dasri (2014)
In the past several decades, extensive amount of research work has been done to understand the fundamental characteristics of the electrical breakdown. Breakdown voltage is a phenomenon where the quantity of an electrical force is required to transform the electrical properties of an object. Many factors that lead to the breakdown voltage are still not fully discovered. These factors are including the physical parameters of the electrodes (sphere, plane, point etc.) and also the environmental conditions. In electrical power system, high voltage (HV) power equipment is mainly subjected with spark over voltage. In this study, point electrode and plane electrode have been used for the experimental study of the short air gap. The electrodes are vertically aligned. In order to simulate the performance characteristic of the air breakdown voltage and maximum electric field between the conducting point and plane electrodes, the electrodes is taken into considered in this work using FEMM simulation. The air breakdown voltages between the electrodes (point and plane) are measured by conducting the air breakdown voltage experiment in high voltage laboratory and corresponding electrical field strength. The electrodes gap distances are being varied to 5 different gaps which are 5mm, 10mm, 15mm, 20mm and 25mm. In order to achieve maximum strength in such a field, the point of the highest stress is controlled. From the experiment, it was established that the point at the electrode that produces maximum electric field is at the point with the smallest area or width. As for point electrode, the smallest area is at the angle of the electrode. Besides, it shows that the electrical breakdown characteristic is affected by the strength of the impulse voltage. Higher gap distance between the electrodes will result higher breakdown-impulse voltage while higher breakdown-impulse voltage will produce higher field intensity.